Uncovering Student Ideas in Primary Science, Volume 1 : 25 New Formative Assessment Probes for Grades K-2. - Keeley, Page (Uncovering Student Ideas in Science., 2013)
What ideas do young children bring to their science learning, and how does their thinking change as they engage in ""science talk""? Find out using the 25 field-tested probes in the newest volume of Page Keeley's bestselling Uncovering Student Ideas in Science series, the first targeted to grades K-2. Uncovering Student Ideas in Primary Science is an invaluable resource for classroom and preservice teachers and professional development providers. This age-appropriate book will help you teach more effectively by starting with students' ideas and adapting instruction to support conceptual change.